KAJIAN GEOTEKNIK TERHADAP FORMASI TANJUNG DI PIT SAYUNA, SATUI, KALIMANTAN SELATAN, DENGAN MENGGUNAKAN METODE SLOPE MASS RATING - -, Geni Dipatunggoro; -, Zufialdi Zakaria (Bulletin of Scientific Contribution, 2012)
Lithology of Tanjung Formation from the oldest to the youngest layers consists of siltstone, mudstone, dan carbonaceous mudstone or sandstone layers with four coal seams. Strike of joint varied N28ºE to N48ºE, N188ºE to N245ºE and N284ºE to N354ºE, and dip of joint varied 52º to 88º (very steep). Weathering conditions of rocks at the surface are moderately weathered (WM) to slightly weathered (WS) stage, and some of this surficial soils are at highly weathered (WH) stage as top soisl. In the bor holes these kinds of weathering stages (WM and WS) are characterized by both law core recovery dan RQD. Sedimentary rock of layer the joint to formed rock blok is discontinuity plane (bedding plane dan joint). The classification system is according to Rock Mass Rating (RMR) after Bieniawski, 1973 to determine the Slope Mass Rating (SMR) resulting maximum angle of cut slope of the rock mass in a stable condition. Rock Mass Rating (RMR) of penetrated rocks of the Tanjung Formation in Bore Hole No. AW-1, AW-2, and AW-3 range from 35 to 70, 40 to 50, and 29 to 60 respectively. The class numbers of the rock mass are II and III in general, suggesting that yhe rock masses are stable (class II) to partially stable (class III), but in Bore Hole AW-1 and AW-2 at the depth ranging from 39.45 to 45.30 meters and 04.75 to 27.84 meters (3 rock masses) respectively class IV occur characterizing the instable rock masses.